Pengaruh Konseling Kelompok Teknik Behavior Contract Terhadap Peningkatan Kedisiplinan Belajar Siswa Kelas VII B SMP Negeri 48 Samarinda Tahun Ajaran 2024/2025 - Tri Nova Ambarwati; Rury Muslifar; Dwi Nugroho Hidayanto; Syarifudin Muslifar (Institut Agama Islam Negeri Curup, 2026)
This study was motivated by the low level of learning discipline among students of Class VII B at SMP Negeri 48 Samarinda, as indicated by frequent tardiness, failure to bring learning materials, and leaving the classroom during lessons. The purpose of this research was to determine the effect of group counseling using the behavior contract technique on improving students’ learning discipline. This research employed a pre- eksperimental design with a one-group pretest-posttest format and a quantitative approach. The subjects were selected using purposive sampling, involving a total of five students. The results showed an increase in students' learning discipline scores after the intervention. The average pretest score was 56.20, which increased to 70.00 on the posttest. A paired sample t-test revealed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest scores. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted, meaning that group counseling with the behavior contract technique had a significant effect on improving students’ learning discipline.